Serbia under the swastika : a World War II occupation - Prusin, Alexander Victor 1955-2018 (The history of military occupation, 2017)
"Following the March 1941 coup d'etat and the new Yugoslav government's refusal to ratify the Tripartite Pact, Germany led an axis invasion of Yugolslavia. Hitler blamed Serbia and the Serbs as the main culprits in the coup. In reprisal, the German military made Serbia into a rump condominium, exploiting it as a strategic base, and as a source of raw materials and cheap labor. In the historiography of World War II in Yugoslavia, the most studied aspect has been guerilla warfare. Western scholars have focused on the regions of the most intense fighting in Bosnia, Herzegovina, and Croatia while wartime Serbia is only mentioned in passing. In "Serbia Under the Swastika," Alexander Prusin focuses on the German occupation of Serbia--the political heartland of pre-World War II Yugoslavia--combining political history with social analysis to explore the interaction between German occupation policies and the forces of resistance and collaboration. Prusin argues that the German occupation policies reflected the rivalries between those who promoted the expansionist and racial vision of the "New Order" and those who advocated a more rational and flexible approach, which entailed a closer reliance on the collaborationist administration and police. Meanwhile, while the situation in Serbia appeared less volatile than in other parts of Yugoslavia, the German occupation policies served as a catalyst for the ferocious internecine conflict between the three native Serbian forces - the Partisans, the nationalist Chetniks, and the pro-German collaborationist regime. However, even as they were locked in a ferocious struggle, the forces of collaboration and resistance often overlapped"--